HISTORY LEARNING MODEL BASED ON THE CONCEPT OF SOEKARNO TO IMPROVE THE STUDENT’S LEADERSHIP IN SMAN 1 PONGGOK BLITAR - Pradeta, Fandu Dyangga; Agung S, Leo; Joebagio, Harmanu (HISTORIKA, 2019)
This development research aims to : (1) analyze and describe the teaching of history earning in SMAN 1 ponggok, (2) Develop history learning model based history Soekarno`s thought leadership to improve student attitudes, (3) examined the effectiveness of the teaching of history-based models Soekarno`s thought leadership to improve student attitudes.                                                                                            This research and development are conducted based on the concept that was created by the Borg and Gall. The step Implementation in the study include preliminary studies, learning models development, and test the effectiveness of the model. The feasibility of data analysis model using a Likert scale with a range 5. whereas effectiveness test using the test model of T-Test                                                                        Based on the research results, more teacher to use the lecture method (teacher centered). The level of student leadership attitude is considered relatively low. Most students have known yet, that the Soekarno’s thought has a great influence on the nation of Indonesia. The steps of this research are divided into several stages they are preparation, implementation and conclusion.                                                The validation by experts taken into consideration to enhance the model to be developed in the try out step. Model validation test results obtained by value of 4.50 (good), validation RPP obtained value of 4.71 (good), validating a matter with a value of 4.72 (good) and the validation of teaching materials / material obtained value of 3.84 (good). The T-Test Results of 5.135 with a significance level of 0.000 <0.025 so mean before and after treatment are not the same experimental class. Thus the history of the developed learning model effectively to improve student achievement and leadership attitudes.